Мультимодальність анімованих вебкоміксів - Єфименко, Вікторія Антонівна (Київський національний університет імені Тараса Шевченка, 2025)
Характерною рисою сучасних коміксів є їх трансмедіальність, коли практики сторітелінгу поширюються з друкованих на цифрові медіа. До таких трансмедіальних адаптацій належать анімовані вебкомікси, які поєднують ключові риси друкованих коміксів з анімацією. Ця стаття присвячена мультимодальним аспектам анімованих вебкоміксів, зокрема анімованого вебкоміксу «Вартові», створеному на основі серії коміксів «Вартові» Алана Мура й Дейва Гіббонса. Перехід до цифрового медіума приніс коміксам такі нові елементи, як відео та звук. Мультимодальний дискурсивний аналіз анімованих вебкоміксів включає дослідження крос-модальної когезії та взаємодії між текстом й ілюстрацією.

A characteristic feature of contemporary comics is their transmediality, in which practices of storytelling expand from print to digital media. Animated webcomics belong to such а type of transmedia adaptation, combining the key features of print comics with animation. This paper focuses on multimodal aspects of animated webcomics, namely, the animated webcomic Watchmen, based on the Watchmen comic book series by Alan Moore and Dave Gibbons. Transition to a digital medium results in enhancements to the comics medium, such as videos and sound. Multimodal discourse analysis of the animated webcomic centres on cross-modal cohesion and text-image relations. Cross-modal cohesion is traced by identifying how the protagonist is presented and tracked, then by constructing identity chains for characters, objects and settings. These chains containing visual, verbal and aural elements demonstrate how different modes interact to make the narrative coherent.
Multimodality of Animated Webcomics
Keywords: комікси; анімовані вебкомікси; цифрові комікси; трансмедіальність; мультимодальність; крос-модальна когезія; взаємовідношення між текстом та ілюстрацією; comics; animated webcomics; digital comics; transmediality; multimodality; cross-modal cohesion; text-image relations